Sex differences in arterial stiffness and blood pressure following resistance exercise - Kappus, Rebecca M.; Rushing, Caroline C.; McShea, Kaitlin T. (International Journal of Sports Medicine, 2025)
Physiological responses to stressors provide insight into future disease risk and sex differences in response to and recovery from stressors, such as a hypertensive stimulus, provide understanding of cardiovascular control. The purpose of this study was to determine sex specific responses to an acute resistance exercise bout in central and peripheral blood pressures and arterial stiffness. Twenty-five young males and females who had not engaged in resistance training over the previous year underwent measurements of aortic, carotid, and brachial blood pressures, and carotid and aortic arterial stiffness measurements before, immediately after, and 30 minutes following a full-body resistance exercise bout. Resistance exercise resulted in increased carotid systolic pressure and increased aortic in males only. Both males and females increased carotid stiffness, but males had a greater increase in stiffness that remained elevated while females returned to baseline by 30 minutes post. These findings highlight that blood pressure and arterial stiffness responses to an acute bout of resistance exercise are sex-specific and vary based on measurement timing and location within the arterial tree. Females do not display the same increases in aortic stiffness and central pressures and did not have the same magnitude of carotid stiffness increases as seen in males.
Keywords: beta stiffness; arterial compliance; pulse wave velocity; aortic blood pressure; MPS carotid blood pressure